The Relationship between Parent’s Role in Managing Screen Time and the Incidence of Speech Delay in Children Aged 1-3 Years at Tanah Kalikedinding Primary Health Center: Hubungan Peranan Orang Tua dalam Mengatur Screen Time dengan Kejadian Keterlambatan Bicara pada Anak Usia 1-3 Tahun di Puskesmas Tanah Kalikedinding - Natasya, Amanda Putri; Erny; Retno Dwi Wulandari (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2025)
Background: Speech delay is a condition in which a child does not achieve speech abilities appropriate for their developmental stage. One of the risk factors influencing speech delay is the role of parents in regulating screen time. Objective: This study aims to determine whether there is a relationship between the role of parents in managing screen time and the incidence of speech delay in children aged 1–3 years. Method: This study is an observational analytic study with a cross-sectional approach, using the chi-square test. Results: The chi-square test yielded a p-value of 0.166, which is greater than 0.05. Conclusion: This study found no significant relationship between the role of parents in regulating screen time and the incidence of speech delay in children aged 1–3 years.